(untitled) (Journal of Forestry, 2025)
In the study, a hierarchical model – based on ecological land classification and mapping were carried out in Gölhisar district with vegetation groups. The presence-absence data of woody plant species were recorded in 398 sample areas in the district. In the study, elevation, slope, aspect, radiation index, topographic position index and bedrock variables required for model-based classification and mapping processes were created. In the statistical evaluation process, firstly, distinction groups were formed by clustering analysis, and then model groups were formed by classification tree techniques. The Chi-square test was applied to determine the relationship between the sub-sampling areas in the groups obtained from clustering analysis and the sub-sampling areas in the model groups obtained from the classification tree technique. As a result of these procedures, a total of four different vegetation groups were obtained in the distirict by adhering to the hierarchical distinction principle. In the last stage, the regionalization process was carried out by using the variables structuring the tree model in the classification tree technique, and thus the tree model obtained was mapped. As a result of this study, Gölhisar district was divided into four different vegetation groups. In consequence of this hierarchical vegetation classification, the most important variables were determined as elevation, radiation index, topographic position index, and bedrock types in the district. While the first and second groups of the separated vegetation groups correspond to the upper parts of Eu – Mediterranean and Supra – Mediterranean climatic zones, it is possible to say that the third and the fourth groups correspond to the Mountainous (above 1200 – 1300 m) and Oro – Mediterranean climate zone.